A study on the pattern of selfie culture among university students in Bangladesh - Mim, Moriom Begum; Asaduzzaman, ASM (Universitas Negeri Yogyakarta, 2024)
This study endeavors to explore the determinants behind the prevalence of selfie culture in the light of self-presentation strategies. It applied Erving Goffman's (1959) Self-Presentation theory to scrutinize the pattern of selfie culture among university students in Bangladesh. Following a qualitative methodology, semi-structured interviews were conducted among 20 participants as a purposive sample age range from 20 to 25 years old. The results demonstrate that the participants tend to invest considerable attention to take selfies, afterward use filters to maximize the